Device-Level Photonic Memories and Logic Applications Using Phase-Change Materials - Cheng, Zengguang (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.